A 0.23‐in. High‐Resolution OLED Microdisplay for Wearable Displays. Issue 1 (June 2014) - Asaki, Reo; Yokoyama, Seiichi; Kitagawa, Hideyuki; Makimura, Shingo; Abe, Fumiaki; Yamazaki, Takashi; Kato, Takayoshi; Kanno, Michihiro; Onoyama, Yusuke; Hasegawa, Eiji; Uchino, Katsuhide
Abstract A 0.23 inch nHD+ OLED microdisplay has been developed with high‐resolution 7.8μm pixel pitch, long life, and lower power consumption than prior OLED microdisplays. This newly developed OLED microdisplay is suitable for wearable displays and viewfinders. A 0.39 inch XGA and 0.7 inch Full‐HD microdisplay will also be discussed.